Evaluation of Teacher E-Performance Implementation Based on GTK Rooms in Kotamobagu: CIPP Model Analysis - Tiwa, Violita Anita (Devotion : Journal of Research and Community Service, 2025)
This study aims to evaluate the implementation of the E-Kinerja policy as a digital system for reporting and developing teacher performance through the Ruang GTK platform in Kotamobagu. The research is important because nationally scaled digital systems often overlook technical readiness, human resources, and local conditions. The method applied is a qualitative approach using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through in-depth interviews, observations, and document analysis with 15 key informants, including education officials, supervisors, principals, and teachers. The results show: (1) varied understanding of policy objectives among implementers, (2) unequal access to infrastructure and technical training, (3) implementation that remains largely administrative, and (4) limited use of Ruang GTK, especially among senior teachers. In conclusion, the CIPP-based evaluation reveals a gap between policy design and field implementation, with inconsistencies between input, process, and product that reduce effectiveness. While the system promotes accountability and measurable reporting, challenges such as digital literacy and server reliability remain significant barriers. The impact of this research lies in its contribution to digital education governance studies, emphasizing the need for adaptive, participatory, and context-sensitive policy design. The findings suggest strengthening infrastructure, expanding training, and simplifying applications to improve the effectiveness of digital platforms like Ruang GTK in diverse regional contexts.